Interface design of stretchable and environment-tolerant strain sensors with hierarchical nanocellulose-supported graphene nanocomplexes. (January 2023) - Zhu, Sailing; Lu, Ya; Wang, Shaolin; Sun, Haoyu; Yue, Yiying; Xu, Xinwu; Mei, Changtong; Xiao, Huining; Fu, Qiliang; Han, Jingquan
Graphical abstract: Highlights: A high-performance elastomer is developed via an interface design strategy. Modified nanocellulose can disperse graphene and improve the polymer interface. The composite conductive elastomer is tough, stretchable and anti-fatigue. The sensor is sensitive, stretchable, durable and environmentally stable. The sensor can detect full-range human motions and subtle acoustic vibrations. Abstract: With the development of wearable electronics, designing a strain sensor with high sensitivity, stretchability, durability and environmental stability is necessary but remains challenging. Herein, a high-performance conductive elastomer is reported by incorporating hierarchical cellulose nanocrystal/graphene (MCNC-GN) nanocomplexes into polydimethylsiloxane (PDMS) matrix. MCNCs serve as the dispersant to form stable MCNC-GN nanocomplexes, and improve their interfacial bonding with PDMS. The composite elastomer possesses excellent tensile strength (∼4.82 MPa), elongation at break (∼142.4 %), electrical conductivity (∼1.0 S m −1 ), anti-fatigue and environment-tolerant property due to the synergetic entanglement between MCNC-GN and PDMS molecules. It also has a sensitivity (gauge factor of ∼ 173.17), wide sensing range (∼100 %) and long-term durability, which can monitor both small/large-scaled and complex human motions, as well as subtle acoustic vibrations even under harsh conditions. This work provides a promising material platform for full-range human body motion detection and acoustic sensing, demonstrating great potentials in next-generation wearable electronics.